The Effect of Price and Service Quality on the Purchasing Decision for Kids Clothes Barbie Brand at PT. Matahari Departement Store, Tbk, Medan Fair Plaza Branch.: Evi Novalin Bako - Evi Novalin Bako; Mawati halawa (Institute of Computer Science (IOCS), 2022)
The purpose of this research is to determine the effect of Price and Service Quality on Purchasing Decisions for Kids Clothes Barbie Brand at PT. Matahari Departement Store, Tbk Medan Fair Plaza Branch. The population in this research is the consumers of PT. Matahari Department Store, Tbk Medan Fair Plaza Branch, totaling 1,155 consumers. The sampling technique used the Slovin formula. The sample in this research is 92 respondents. Data was collected using a questionnaire in accordance with the indicators of each variable used. The data analysis technique uses is descriptive analysis and multiple linear regression. The result of the test (t) or partial test shows that the price has a positive and significant effect on purchasing decisions which is t count = 9.106 > t table 1.986. Service Quality Variables also have a positive and significant effect on purchasing decisions which is t value = 9.654 > t table 1.986 and simultaneously (F test) Variable Price and Service Quality (0.000) are smaller than alpha 5% (0.05) or required significance value of F is less than 5% or 0.05 or the Fcount value = 47.014 > Ftable 3,10.